Bangunan Sultan Idris Shah, JAIS / Muhammad Amir Farhan Zulkafli ... [et al.] - Muhammad Amir Farhan, Zulkafli; Muhammad Syaril Ikhwan, Shafie; Fatin Nadhirah, Hilmi; Nur Ainin Sofiya, Rasnol’Aided; Nurul Najah, Nasrul (2019)
This project report entitled to “Integrated Final Project” with a case study, Bangunan Sultan Idris Shah. The aim of this assignment is to learn the maintenance management of an existing building which is Bangunan Sultan Idris Shah. The study includes cleaning services, building elements, infrastructure works, landscaping works, mechanical and electrical works, defects and financial. In addition, the process of identifying the maintenance management strength and theweakness of the team for managing the building thoroughly. Every details needed such as the building backgrounds and team backgrounds were collected through interviewing with the officers. Secondary data are based on the reports and documents given by the officers. There are numerous tools used to indicate the data such as cash flow statement or schedule statement. Charts and table used for better understanding. In summary, Bangunan Sultan Idris Shah is using traditional methods in certain part because they find is easier to handle. Furthermore, there are common defects that can be find such as leaking and dampness. The primary income source is from the state.